2018
DOI: 10.1101/437202
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide disruption of DNA methylation by 5-aza-2’-deoxycytidine in the parasitoid waspNasonia vitripennis

Abstract: 25DNA methylation of cytosine residues across the genome influences how many genes and phenotypes 26 are regulated. As such, understanding the role of DNA methylation and other epigenetic mechanisms 27 has become very much a part of mapping genotype to phenotype, a major question in evolutionary 28 biology. Ideally, we would like to manipulate DNA methylation patterns on a genome-wide scale, to 29 elucidate the role of epigenetic modifications in phenotypic expression. Recently, the demethylating 30 agent 5-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…Boldfacing indicates statistical significance. study in Nasonia vitripennis, also showing a lack of uniform demethylating effect of 5-aza-dC treatment across sites (Cook et al 2019). We observed the same result for each of the three categories of genes we tested: there was no reduction in DNA methylation in highly methylated genes, nor in genes previously shown to have varying methylation levels, nor in genes involved in lipogenesis, a metabolic process that has been suggested to be epigenetically regulated.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Boldfacing indicates statistical significance. study in Nasonia vitripennis, also showing a lack of uniform demethylating effect of 5-aza-dC treatment across sites (Cook et al 2019). We observed the same result for each of the three categories of genes we tested: there was no reduction in DNA methylation in highly methylated genes, nor in genes previously shown to have varying methylation levels, nor in genes involved in lipogenesis, a metabolic process that has been suggested to be epigenetically regulated.…”
Section: Discussionsupporting
confidence: 72%
“…In bumble bees, 5-aza-dC has an effect on overall DNA methylation, but its effect is erratic, as hyper-and hypomethylation were both observed after 5-aza-dC treatment (Amarasinghe et al 2014). A similar variable effect of 5-aza-dC treatment on methylation status of individual CpG sites was also found in a genome-wide study of methyl-ation in N. vitripennis (Cook et al 2019). Our study adds to this growing body of literature by showing a lack of consistent demethylating effect of 5-aza-dC in N. vitripennis.…”
Section: Discussionsupporting
confidence: 54%
“…Ellers et al (2019) raised the valid concern that the anti-metabolic activity of 5-aza-dC could result in a decline in the physical condition of Nasonia vitripennis females, indirectly producing observed phenotypic differences through a mechanism independent of DNA demethylation. Whilst we have shown that 5-aza-dC at the dosage used in our original experiment produces altered methylation patterns (above; Cook et al 2018), the possibility of confounding side-effects should not be ignored. We do note, however, that an effect of condition-dependent sex allocation has yet to be elucidated in Nasonia vitripennis, although pathological side-effects of any given chemical exposure cannot be discounted.…”
Section: Quantifying the Efficacy Of 5-aza-dcmentioning
confidence: 88%
“…Recently we carried out a genome-wide analysis of the demethylating capacity of 5-aza-dC in Nasonia vitripennis (Cook et al 2018). Briefly, female wasps were exposed to one of three 5-aza-dC exposure regimes: 1) 20% sucrose for 24h, 2) 20% sucrose supplemented with 10 µM 5-aza-dC for 24h and 3) 20% sucrose supplemented with 10 µM 5-aza-dC for 48h.…”
Section: Quantifying the Efficacy Of 5-aza-dcmentioning
confidence: 99%
See 1 more Smart Citation